The Practical Challenges and Optimization Strategies for Cultivating Digital Literacy among Nursing Students in Higher Education Institutions - Liu, Chao; Qi, Wenqian; Li, Ping; Li, Yuanmeng; Wang, Xin; Liu, Mengmeng; Qu, Chenfei (Education Insights, 2026)
The rapid digital transformation of healthcare systems is fundamentally reshaping nursing practice, establishing digital literacy as an indispensable core competency for future nursing professionals. However, nursing students in higher education institutions face multiple, interrelated challenges in developing the digital capabilities required to adapt to contemporary, technology-rich healthcare environments. This paper systematically reviews and synthesizes recent empirical research and theoretical contributions to analyze the practical difficulties impeding the cultivation of digital literacy among nursing students and to propose comprehensive optimization strategies. Drawing upon frameworks such as the Technology Acceptance Model and Experiential Learning Theory, the analysis identifies four primary categories of challenges: individual-level barriers, including insufficient digital competence, low self-efficacy, and psychological resistance; institutional-level deficiencies, such as curriculum gaps, inadequate faculty preparation, and limited infrastructure; pedagogical challenges, including a persistent theory–practice disconnect and insufficiently interactive teaching methodologies; and systemic inequalities related to the digital divide and resource constraints. Based on five interrelated dimensions—curriculum integration, pedagogical innovation, faculty development, infrastructure upgrading, and policy support—this paper proposes targeted optimization strategies. Particular attention is devoted to evidence-based approaches such as design-oriented learning, simulation-based training, and experiential learning methodologies, which have demonstrated effectiveness in enhancing informatics and digital literacy among nursing students. The review concludes that cultivating digital literacy requires a coordinated, multi-stakeholder approach that integrates technical skills with cognitive, ethical, and sociocultural dimensions of digital competence, offering practical implications for educators, administrators, and policymakers.